2014
DOI: 10.1039/c4ta04954c
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillated cellulose-reinforced bio-based poly(propylene carbonate) with dual shape memory and self-healing properties

Abstract: A novel biological friendly shape memory polymer and self-healing polymer based on poly(propylene carbonate) (PPC)/microfibrillated cellulose (MFC) was prepared. MFC was firstly modified by a one-step mechanic-chemical approach involves ball milling and esterification reaction. In this way MFC could be incorporated into PPC up to 20 wt% with excellent dispersion. The formation of "MFC network" structure in the PPC matrix was verified via scanning electron microscopic and the strong interfacial interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 41 publications
2
69
0
Order By: Relevance
“…Pro Plus Image estimates the size of white dots to be in the range of 20–30 nm, which is similar to the diameter of CNCs . On the other hand, SEM was employed to observe the dispersion state of MFC fibers in the PPC matrix, and the results are shown in Figure ll–qq . Compared with the smooth surface of neat PPC, all PPC/MFC presented typical crumpled morphologies that became more visible with the increasing content of MFC .…”
Section: Characterizationmentioning
confidence: 96%
See 2 more Smart Citations
“…Pro Plus Image estimates the size of white dots to be in the range of 20–30 nm, which is similar to the diameter of CNCs . On the other hand, SEM was employed to observe the dispersion state of MFC fibers in the PPC matrix, and the results are shown in Figure ll–qq . Compared with the smooth surface of neat PPC, all PPC/MFC presented typical crumpled morphologies that became more visible with the increasing content of MFC .…”
Section: Characterizationmentioning
confidence: 96%
“…To obtain PPC/DMF NCs, certain amount of MFC/DMF solution was added into the PPC/DMF solution under vigorous stirring for 2 h, and then the homogeneous PPC/MFC/DMF solution was poured into glass frames. The casting films were dried in an air‐circulating oven at 70 °C to quickly remove DMF and then dried in a vacuum oven at 60 °C for 48 h . By using a solvent‐exchange and solution casting approach, a high‐content of GO was incorporated into a soft biodegradable CO 2 ‐based PPC up to 20 wt% with excellent dispersion .…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was found that the treatments of switchgrass did not have any effect on the mechanical properties compared to that of the untreated switchgrass composites . Qi et al . developed PPC/acetylated micro‐fibrillated cellulose (MFC) composites by solution casting.…”
Section: Ppc Compositesmentioning
confidence: 99%
“…Nowadays, selfhealing materials [6][7][8][9][10][11][12] are under rapid development to improve the lifetime, safety, energy efficiency and environmental impact of synthetic materials. The past few decades have witnessed a rapid development in exerting such features into articial systems where polymers are used for self-healing applications.…”
Section: Introductionmentioning
confidence: 99%